하악 후구치부에 발생한 주변성 법랑모세포종 - 유태훈; 최승현; 나종찬; 안미영; 이준; 윤정훈 (대한구강악안면병리학회지, 39(1), 2015)
Peripheral ameloblastoma, a rare and unusual variant of odontogenic tumor, representing 1% of all ameloblastomas. The extraosseouslocation is the peculiar feature of this type of tumor, which is otherwise similar to the classical ameloblastoma. This paper describesa case of peripheral ameloblastoma in a 43-year-old female affecting the left retromolar pad area of the mandible which was clinicallydiagnosed as a pyogenic granuloma. Histologically, the tumor showed of follicular ameloblastoma in continuity with a surface oralepithelium. KCI Citation Count: 0